The Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues papers provide details of the sources and uses of the non-financial corporation saving and highlights the role of multinational corporations (MNCs). The paper also discusses the implications to the external sector assessment and policy recommendations. The large Dutch international investment position reflects its status as an international corporate center. The study shows that large trade surpluses and small primary income balances are consistent with the dominance of MNCs in the Netherlands' external positions. Separating MNCs' activities from the Dutch current account for the external sector assessment is expected to help identify underlying policy distortions. Separating MNCs' activities would help identify imbalances of other economic sectors. The small and medium enterprises are stagnant and remain financially constrained. Small household net saving hides the fact that households are still highly leveraged, and their consumption constrained by a stagnating disposable income. Therefore, improving statistics and separating MNCs' activities from both internal and external accounts would help identify domestic policy distortions and address imbalances effectively.